Cytoplasmic and peroxisomal catalases of the guinea pig liver: evidence for two distinct proteins - Bulitta, Clemens; Ganea, Christina; Fahimi, H. Dariush; Völkl, Alfred (Biochimica et biophysica acta. Protein structure and molecular enzymology, 1996)
Catalase, a peroxisomal marker enzyme in the liver of most mammals, is found by immuno-electron microscopy in guinea pig (GP) hepatocytes not only in peroxisomes, but also in the cytoplasm (Beier et al. (1988) Eur. 7. Cell Biol. 46, 129-135). We have been able to distinguish in GP liver homogenates between the cytosolic catalase and that part of the enzyme activity which is due to leakage of the enzyme from peroxisomes by adding 4% polyethylene glycol to the homogenization medium. This approach revealed that approximately 40% of the total catalase activity and almost all of α-hydroxy-acid oxidases are peroxisomal, while 60% of catalase is of genuine cytosolic origin. The cytosolic; and peroxisomal catalases of guinea pig were purified to homogeneity and were analyzed by SDS-PAGE and isoelectric focussing. The cytosolic catalase exhibited a slightly higher Mr (≈ 1000) and a less acidic pI than the peroxisomal enzyme. Limited proteolysis and amino-acid analysis revealed also slight differences between the two molecular forms of catalase. Total RNA was isolated from guinea pig liver and translated in vitro by using a rabbit reticulocyte lysate system. Immunoprecipitation with an antibody against guinea pig catalase followed by high-resolution polyacrylamide gel electrophoresis revealed two polypeptide bands differing slightly in Mr. These observations suggest strongly, that cytoplasmic and peroxisomal catalases in guinea pig liver are two closely related but distinct proteins.